Penggunaan Media Grafis (Peta Konsep) Dalam Pembelajaran Sejarah Untuk Mempermudah Pemahaman Siswa Kelas V Mi Darul Ulum Bojonegoro - Yulia Pramusinta (Universitas Islam Lamongan, 2017)
Abstract: The teaching medium is a knowledge of the teaching methods used by a teacher or instructor. Methods are the means used to achieve the established goals. Another technique is the presentation technique that is mastered by the teacher to teach or present the lesson materials to the students in the classroom, so that the lesson can be absorbed, understood and used by the students well. The better the teaching method, the more effective the achievement of the goal. Motivation is a change of energy within a person characterized by the emergence of